Evolutionary history of the Pelasgus minnows (Teleostei: Leuciscidae), an ancient endemic genus from the Balkan Peninsula - Viñuela Rodríguez, Nuria; Šanda, Radek; Zogaris, Stamatis; Vukić, Jasna (Molecular phylogenetics and evolution, 2021)
The Balkans are one of the European biodiversity hotspots, hosting outstandingly rich, yet threatened, flora and fauna. This region hosts one of the richest endemic freshwater ichthyofauna in Europe, including several genera occurring exclusively here. One of these is the genus of the primary freshwater minnows Pelasgus, which was designated only in 2007. The genus is one of the most ancient genera of the family Leuciscidae and comprises seven small-bodied species, inhabiting slower, well-vegetated courses of rivers. This work is the first molecular multilocus phylogeny of the genus, based on one mitochondrial and three nuclear markers. In total, 305 individuals across almost entire distribution range of the genus were analysed. We inferred the evolutionary history of the species by comparing the results of our calibrated multilocus coalescent species-tree to palaeogeological events. The diversification of the genus started in the early Miocene and continued through to the beginning of Pleistocene. We identified the regions of the oldest colonization by Pelasgus, the drainages of the ancient lakes Ohrid and Prespa, and the southernmost part of the Peloponnese, hosting Pelasgus minutus, P. prespensis and P. laconicus, respectively. We showed that P. prespensis is not endemic to Lake Prespa, as previously thought; it occurs also in the Albanian River Devoll. This corroborates the emerging opinion that the endemic taxa of ancient lakes evolved within larger-scale historic drainages and not only within the lakes. Our results showed that the species with the most recent common ancestor of the early Pliocene origin, P. thesproticus, P. epiroticus, P. stymphalicus and P. marathonicus, have neighbouring distribution ranges. Pelasgus epiroticus is especially interesting, not only for its pronounced genetic diversity with a geographic pattern, but also for being found at three localities within the native distribution range of P. stymphalicus as a result of a translocation. At two of these localities, we identified hybrids between the two species, and at one of them, the genetically pure native species was not found at all. This points to a threat of the loss of the native ichthyofauna due to unintentional translocations.
Keywords: Animals; Multilocus phylogeny; DNA, Mitochondrial; jezera; Cyprinidae; lidé; Balkánský poloostrov; máloostní; Hybridization; Endemic species; Phylogeny; mitochondriální DNA; Balkan Peninsula; Cypriniformes; Lakes; zvířata; fylogeneze; Time-calibrated species tree; Humans